Pengaruh Latihan Variasi Plyometric terhadap Peningkatan Kemampuan Vertical Jump pada Atlet Putra Klub Bola Voli Usia Remaja - Imandaqurani, Deva; Pratama, Henri Gunawan (SPRINTER: Jurnal Ilmu Olahraga, 2024)
The jump smash technique relies on the strength of the leg muscles. Leg muscles are the most important muscle group that supports jumping. Plyometric is a type of exercise that forces muscles to work quickly. Volleyball athletes must use different plyometric training methods before performing vertical jumps. The research method used a "one group pretest-posttest design" with a total sampling of 20 male volleyball players. This study used A vertical jump test to obtain pretest and posttest data. Data analysis using T-Test. The results showed a significant improvement in vertical jump ability after 18 training sessions, with a posttest score between 34 and 57 and a percentage increase of 24.3%. Statistical analysis showed a t-count of -18.685 with a significance of 0.000, indicating that plyometric exercise had a significant positive effect. These results can help sports coaches and teachers improve volleyball athletes' jump ability.